Export, FDI and Productivity – Evidence for French Firms - Dirk Engel; Vivien Procher (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The decision of companies to enter international markets, either via exports or foreign direct investment (FDI), has been postulated by the self-sorting model of Helpman, Melitz and Yeaple (HMY, 2004). In the strict sense, the theoretical predictions of HMY only apply to firms that become engaged in market- driven (horizontal) FDI. Hence, in this paper we apply more precise methodologies to test the HMY hypothesis. First, we classify MNEs according to the underlying motives for investing abroad (market-driven vs. resource-driven FDI). Second, we highlight the role of productivity growth in the post-entry period. Our findings suggest that productivity affects the FDI decision considerably whereas expected feedback and learning effects of FDI on productivity are remarkably lower. We further detect that more market-driven MNEs exhibit a higher productivity than comparatively less market-driven MNEs.
Keywords: F10; F23; D21; D24; 330; Foreign direct investment; horizontal and vertical FDI; multinational enterprises; productivity; Direktinvestition; Multinationales Unternehmen; Wettbewerbsstrategie; Exportindustrie; Produktivität; Frankreich